Converage and Broadcast Media Functions : Advertising Media, Entertainment Media, Information Media, Service Media - Winda Kustiawan; Tri Andini; Dermawan Wijaya Harahap; Adelia Hasibuan; Khairil Anzar; Sahlan Habibi Siregar (Lembaga Pengembangan Kinerja Dosen, 2026)
Broadcast media encompassing television, radio, public broadcasting, and digital platforms plays a central and increasingly significant role within the sphere of contemporary societal life. The content presented, particularly in the form of advertising, entertainment, information, and public services, possesses the capability to transform the way individuals access knowledge, consume leisure, and utilize public facilities. This paper aims to elaborate upon and describe these four essential functions of broadcast media, analyze their implications, and delineate the interconnection and functional integration of media amidst the progress of the digital era. In the digital age, these four media functions no longer operate in isolation (siloism) but tend to integrate with one another through the mechanism of convergence within a single platform ecosystem, as evidenced by platforms such as YouTube or TikTok. This convergence facilitates simultaneous and streamlined access for the public to a diverse range of needs. Consequently, this integration necessitates the strengthening of digital literacy among the audience to enable critical content filtering and the mitigation of potential negative impacts. A comprehensive understanding of broadcast media functions constitutes an essential prerequisite for ensuring their optimal utilization for the public good and supporting national development.